Building a Literacy Culture in Elementary Schools: Implementation of a Student Illiteracy Eradication Program - Muh. Alamsyah; Muhammad Ridho Ardani; Ainun Muthaharah Ichwan; Warka Syachbrani (PT. Global Research Collaboration, 2025)
Indonesia, despite being rich in human resources (HR) and natural resources (SDA), still faces major challenges in improving the quality of HR, especially related to low interest in reading and illiteracy problems. Education is the main key in overcoming this problem, with literacy as an important foundation for the development of students' cognitive abilities. This study focuses on the implementation of the illiteracy eradication program at SD Negeri 011 Rappogading through Literacy Strengthening Training for Teachers. This program aims to improve teacher competence in teaching basic literacy and creating a sustainable literacy culture in schools. The results of the study showed a significant increase in teacher competence, changes in the literacy environment in schools, and an increase in student literacy skills by 25%. This program proves that strengthening teacher competence, parental involvement, and creating a conducive literacy environment are very important in overcoming the challenge of illiteracy. Based on these findings, it is recommended to improve educational infrastructure, extend ongoing training for teachers, and involve the community in strengthening literacy culture. With these steps, it is hoped that Indonesia can improve the quality of HR and accelerate the transformation process into a developed country.